Biomass of Eucalyptus Hybrid Plantations under Agroforestrysystem - Mohsin, Faiz; Singh, R. P.; Rajput, D. K. (Indian Forester, 2003)
Eucalyptus hybrid trees grown in stands intercropped with various Mentha and Cymbopogon spp. attained better growth than pure stands at juvenile (2 and 3 yrs.) and advanced (6 and 7 yrs.) ages. Bolewood provided maximum contribution among all the components in pure as well as intercropped stands at all the age group of trees. It was further revealed that the total biomass was highest in the plantation of Eucalyptus hybrid of all the ages intercropped with Mentha spp. It decreased in Cymbopogon spp. but still reained higher than that of pure stands which showed lowest biomass production.